Prognostic significance of acute exacerbations and usual interstitial pneumonia in fibrotic interstitial lung disease - Yun Zhang; Zekai Cen; Qunli Ding; Yanan Ying; Chengna Lv; Tingting Wu (Scientific Reports)
Abstract Fibrotic interstitial lung disease (FILD) is a general term that includes many diseases that manifest as pulmonary fibrosis and are often progressive and associated with high morbidity. However, there are limited data regarding the frequency and prognosis of FILD patients other than those with idiopathic pulmonary fibrosis (IPF). The purpose of this study was to investigate the clinical characteristics and early prognostic risk factors for FILD. This study retrospectively reviewed the data of patients who were diagnosed with FILD between April 2011 and September 2022 in our centre. Ultimately, 194 patients diagnosed with non-IPF fibrotic ILD were screened in our study. Baseline clinical information, pulmonary function tests, and chest images were collected and analysed. Connective tissue disease-related interstitial lung disease (CTD-ILD) (60.3%) was the most common subgroup of FILD and associated with longer survival than the other types of FILD. The age at diagnosis of ILD (64.4 ± 13.5 vs. 70.0 ± 11.6 years, P = 0.001) and the proportion of males, smokers and acute exacerbations (AEs) (13.5% vs. 27.5%, P = 0.026) were significantly higher in the UIP group than in the NSIP group. The Kaplan‒Meier survival analysis showed that the IPF group (HR 1.97, 95% CI 1.05–3.70, P = 0.011) had a worse survival rate than the FILD group, and landmark analyses showed that the survival of FILD patients with the UIP pattern (HR 3.07 95% CI 1.37–6.86 P = 0.006) was significantly shorter than that of FILD patients with the NSIP pattern 48 months after ILD diagnosis. In the multivariate Cox analysis, AEs of ILD (HR 4.17 95% CI 2.24–7.75 P < 0.001) and combined with lung cancer (HR 3.12 95% CI 1.27–7.65 P = 0.013) remained as significant factors that were independently associated with shorter survival. CTD-ILD is the most common subgroup of FILD in our study, and the prognosis is better than that of other types of FILD. Patients with the UIP pattern tend to be older and have a higher proportion of AEs. The prognosis is worse than that of patients with the NSIP pattern in the later stage. AEs and combined with lung cancer are independent risk factors for the prognosis of FILD patients, and more attention should be given to such patients.